Crypto-Jews: the long journey - Hart, Ron D. (Series on tolerance and diversity, 2020)
"For many in the United States, Crypto-Judaism has been shrouded in memory and for others it has become an imagined land that might have been, often with little information about the actual history and heritage of the group. Today, in the American southwest and in parts of Latin America there is a movement to reclaim Jewish identity, and people are describing the memories of Jewish identity with the family and the remnants of Jewish practice. That has sparked interest in learning more about Sepharad, the Spain of the Jews, and the diaspora of Spanish Jews and their cousins, the Crypto-Jews. Myths have grown around the concept of Sepharad sometimes obscuring the realities of what it was. There was a "golden age" for Jews in Spain during the early Muslim period, but as the reconquest heated up and Christian rule replaced that of Muslims, the Jewish experience turned dark until the light of the Jews was put out in Spain. In my experience in New Mexico, I have found that local oral traditions about Jewish family identity or reclaimed Jewish identity can be rich, but in some cases not coinciding with historical information. So, there can be multiple tracks of inherited or imagined information in addition to historical documentation. The belief about the association between Judaism and Spain that is expressed among some is that anyone of Spanish descent must have sangre Judia "Jewish blood". That contradicts what we know of the demographics of Spain, which suggest that at the time of the Expulsion, Jews were a minuscule part of the population, probably close to two percent. Crypto-Judaism is an attempt to draw a historical baseline of established information of what we know about those times and the Crypto-Jewish experience"--